Tecnologia adaptativa aplicada à otimização de código em compiladores - Neto, João José (2003)
The programming memory space of embedded microcontrolled systems is usually limited. Although, compilers nowadays apply optimizing transformations to the embedded software, the lack of memory space can become a critical problem to the designer with the introduction of new features and corrections in the original software. In contrast, workstations hosting development systems for embedded applications are faster and have much more memory. Given this scenario, we have developed a peephole optimizer exploring an adaptive technique that requires more memory and execution time, but is capable to achieve a better compression ratio of the object code than a conventional peephole optimizer. The introduction of an adaptive action enables the algorithm to self-modify its behavior in response to a specific input condition and to search the sequence of optimization rules that best optimizes the object code among the many possible sequences resulted from the superposition of two or more equally applicable optimization rules.